Liberal leviathan : the origins, crisis, and transformation of the American world order - Ikenberry, G. John (Princeton : Princeton University Press, 2011)
In the second half of the twentieth century, the United States engaged in the most ambitious and far-reaching liberal order building the world had yet seen. This liberal international order has been one of the most successful in history in providing security and prosperity to more people. But in the last decade, the American-led order has been troubled. Some argue that the Bush administration, with its war on terror, invasion of Iraq, and unilateral orientation, undermined this liberal order. Others argue that we are witnessing the end of the American era. Liberal Leviathan engages these debates.
Crisis of the old order -- Part I: Theoretical foundations. Power and the varieties of order ; Power and strategies of rule ; Unipolarity and its consequences -- Part II: Historical origins and trajectories of change. The rise of the American system ; The great transformation and the failure of illiberal hegemony ; Dilemmas and pathways of liberal international order -- Conclusion. The durability of liberal international order.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: United States -- Foreign relations -- 21st century; Hegemony; Unipolarity (International relations); États-Unis -- Relations extérieures -- 21e siècle.; Hégémonie.; Unipolarité (Relations internationales); POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; POLITICAL SCIENCE -- History & Theory; Hegemony; Diplomatic relations; Unipolarity (International relations); United States; Hegemonie; Liberalismus; Machtverlust; Weltordnung; USA; Internationale orde; Liberalisme; Buitenlandse betrekkingen; Grote mogendheden; Buitenlandse politiek; Verenigde Staten; Weltordnung; Liberalismus; Hegemonie; Internationale Politik; USA; Internationella relationer; Liberalism; 2000-2099